Dusk a novel - Jose, Francisco Sionil 1924- (New York Modern Library, 1992)
Opportunity knocks for a peasant boy in 19th century Philippines with the outbreak of the Spanish-American war. As an altar boy in his village, Istak is the only person able to read and write, and the Americans give him a job.
Originally published: Po-on. Manila : Solidaridad Pub. House, c1984.
Fi-8950g donated by Prof. Belinda A. Aquino.
Keywords: Philippine fiction (English).; Historical fiction, Philippine; Philippines -- History -- 1898-1946 -- Fiction